Promoting effect of low concentration strontium on photosynthetic performance of Chinese cabbage seedlings: Combined leaf characteristics, photosynthetic carbon assimilation and chlorophyll fluorescence - Erkun Chao; Mengmeng Wu; Dongxue Yue; Yongxue Yuan; Nianwei Qiu; Feng Zhou (Ecotoxicology and Environmental Safety, 2024)
Low concentration strontium (LC-Sr) can promote the growth of plants. In order to explore its promoting mechanism from the aspect of photosynthesis, the leaf characteristics, CO2 assimilation and chlorophyll (Chl) a fluorescence kinetics were investigated with hydroponically LC-Sr-treated Chinese cabbage seedlings. After a 28-d treatment to SrCl2 at different concentrations (0.1, 0.2, 0.5, and 1.0 mmol L−1), we observed an increase in the specific leaf weight (SLW) of Chinese cabbage compared with the control group. Notably, as the strontium concentration increased, a more pronounced improvement trend in the contents of Chl and protein in the leaves was observed, contributing to the enhancement of photosynthesis. However, the statistical differences in Pn among various LC-Sr treatments were not significant. Nevertheless, the leaf starch content exhibited a significant increase after LC-Sr treatments. Additionally, Chl a fluorescence transient has been used as a sensitive indicator of the promotional effect of LC-Sr on photosynthesis. The results of fluorescence parameters showed that LC-Sr treatments accelerated the light reaction speed of leaves (Tfm, dV/dto, dVG/dto), improved the energy utilization efficiency of photosystem (PSI and PSII) (ETo/CSo, ψET,ψRE, δRo, φRo), and ultimately enhanced the photosynthetic performance of leaves (PIabs, SFIabs, DFabs). The increased RCs/CSo and Sm contributed to the enhancement of the light reaction activity of strontium-treated leaves. The LC-Sr treatments had no interference with the calcium absorption, and notably enhanced the photosynthetic capacity of Chinese cabbage, shedding light on potential benefits of LC-Sr for crop cultivation.